From “waiver of indictment” to “withdrawal of indictment”. Remarks on Article 14 § 2 of the Criminal Code - Sowiński, Piotr Krzysztof (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
This article discusses the issues related to the application of regulations included in Art. 14, § 2 of the Criminal Code where the withdrawal of the indictment by the public prosecutor was regulated. Moreover, the results of such an activity and the conditions of its performance were indicated. The rights of the accused and the injured party related to the withdrawal of the indictment and also the prohibition of the re-indictment against the same defendant in relation to the same criminal Act were discussed.

W tekście omówiono problematykę związaną ze stosowaniem przepisu art. 14 § 2 k.p.k., w którym uregulowano tzw. cofnięcie aktu oskarżenia przez oskarżyciela publicznego. Wskazano na skutki tej czynności oraz warunki jej dokonania. Omówiono uprawnienia oskarżonego i pokrzywdzonego związane z cofnięciem aktu oskarżenia, a także zakaz ponownego wniesienia oskarżenia przeciwko temu samemu oskarżonemu o ten sam czyn karalny.
Keywords: indictment; withdrawal of indictment; waiver of indictment; public prosecutor; accused party; injured party; auxiliary prosecutor; criminal proceedings; discontinuation of criminal proceedings; procedural guarantees; akt oskarżenia; cofnięcie aktu oskarżenia; odstąpienie od oskarżenia; oskarżyciel publiczny; oskarżony; pokrzywdzony; oskarżyciel posiłkowy; postępowanie karne; umorzenie postępowania karnego; gwarancje procesowe